Massive digoxin ingestion. Report of a case and review of currently available therapies. - Bremner, W F (1977)
Recent reports of treatment of massive digoxin overdosage have emphasized the success of medical therapy. This report describes a fatal outcome to this problem despite aggressive medical management, including pervenous cardiac pacing and draws attention to deficiencies in current treatment of a serious problem.